The use of anime as a teaching tool in a Japanese as a foreign language classroom / Chan Yee Han - Chan, Yee Han (2017)
Nowadays, with the rapid growth and availability of technology, traditional teaching approaches are often complemented by new innovations such as computer and audiovisual equipment as additional teaching aids along with the textbooks to teach language. Although the use of audiovisual materials, such as movies, dramas, news, and cartoon in language teaching has become a common approach for the language educators, many of them might not be well aware of the option of using anime in the context of teaching Japanese as a Foreign Language (JFL). There has been very little research reported on the practical use of anime in a JFL classroom. The present study was aimed to fill this gap by introducing the use of anime as a teaching tool in a JFL classroom and to understand the JFL students’ experiences of learning the Japanese language and culture through anime in the classroom context. To this end, eleven participants selected from a pilot study were invited to attend a course named “Learning Japanese Language and Culture through Anime” in a local public university. The present study employed the phenomenological research design by collecting qualitative data via participants’ analysis worksheets, learning diaries, and group interview. The findings showed that a JFL classroom could be dynamic and effective with the use of anime as a language and culture teaching tool. Through several classroom activities such as active viewing, reproduction, repetition, freeze framing, and follow-up discussion, productive lessons could be conducted. The analysis of anime dialogues played a very important part in raising the learners’ awareness about language features in anime such as different levels of politeness, casual forms, sentence-final particles, pronouns, honorific suffixes, and proverbs. Apart from effective language and culture learning, the use of anime in the JFL classroom was found to be able to create a motivating learning environment, provide a unique way of learning, strengthen classroom engagement, promote the learners’ critical thinking skill, and stimulate the learners’ extra effort to learn about the Japanese language and culture. On the other hand, the problems of using anime as a teaching tool such as biases towards anime and stereotypes were identified. For successful communication, the learners should have clear understanding not only of the lexicon, grammar, and culture patterns, but also the pragmatic background of the situation. In other words, the learners need to understand how context contributes to meaning in order for them to construct meaningful and effective communication in the foreign language that they are learning. In the case of teaching and learning JFL, the present study has shown that anime could be useful to help the language educators and language learners to achieve these language teaching and learning goals